Focus on adult health : medical-surgical nursing - Pellico, Linda Honan (Wolters Kluwer/Lippincot Williams & Wilkins Health, 2013)
Designed to prepare students to succeed as practicing nurses by focusing on the most important medical disorders and key nursing responsibilities, this title intends to prepare students for the reality of medical-surgical nursing. It teaches students how to think like a nurse, and how to focus quickly on the most critical aspects